APLIKASI STRUCTURAL EQUATION MODEL (SEM) DALAM PENENTUAN ALTERNATIF PENGELOLAAN LINGKUNGAN INDUSTRI KOMPONEN ALAT BERAT BERBASIS PARTISIPASI DAN KEMITRAAN MASYARAKAT - Budi Setyo Utomo; Syamsul Maarif; Surjono Hadi Sutjahjo; Sumardjo Sumardjo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2012)
As a company engaged in the industrial sector by producing certain components and localized in an industrial area, there will be an impact on the environment. These impacts can be positive in the form of employment, reducing dependence on imported heavy equipment, increase in foreign exchange due to reduced imports and increased exports, increased government revenue from taxes, public facilities improvement and supporting infrastructure, and opening up opportunities for other related industries. These impacts can also be negative in the form of environmental degradation such as noise disturbance, dust, and micro climate change, and changes in social and cultural conditions surrounding the industry. Data analysis was performed descriptively and with the Structural Equation Model (SEM). SEM is a multivariate statistical technique which is a combination of factor analysis and regression analysis (correlation), which aims to test the connections between existing variables in a model, whether it is between the indicator with the construct, or the connections between constructs. SEM model consists of two parts, which is the latent variable model and the observed variable model. In contrast to ordinary regression linking the causality between the observed variables, it is also possible in SEM to identify the causality between latent variables. The results of SEM analysis showed that the developed model has a fairly high level of validity that is shown by the minimum fit chi-square value of 93.15 (P = 0.00029). Based on said model, it shows that the company's performance in waste management is largely determined by employee integrity and objectivity of the new employees followed later by the independence of the employees in waste management. The most important factor that determines the employee integrity in waste management in the model is honesty, individual wisdom, and a sense of responsibility. The most important factor in the employee objectivity in waste management is the support of accurate data in each report of waste management by the company and transparency on reports of the company’s activity. While the factors that determine the employee independency is the company's interests, a sense of employee volunteering, and openness between the company and employees. Keywords : heavy equipment industry, management, environment, Structural Equation Model (SEM)